2020
DOI: 10.1071/sr20025
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil humus composition and humic acid structural characteristics under different corn straw returning modes

Abstract: Studying changes in soil humus composition and humic acid (HA) structural characteristics caused by agronomic practices provide insights into the pathways of soil organic carbon (C) stabilisation dynamics. This five-year field study evaluated the effects of straw returning modes on humus composition and HA structure. Treatments included (i) corn straw returned on the soil surface (NTS), (ii) corn straw incorporated into soil within 0–10 cm (MTS), (iii) corn straw incorporated into soil within 0–20 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In this five-year study, retention of corn straw increased SOC content by 25.35%, 10.57% and 9.31% under NTS, MTS and CTS treatments, respectively when compared with CK in the 0-20 cm soil depth (Table 1), and coincides with previous studies (Swanepoel et al, 2018;Pu et al, 2019;Zhang et al, 2019). As a C rich substance, application of corn straw serves as a C substrate for microbes and replenishes SOC content (Ndzelu et al, 2020), thereby contributing to the build-up of SOC. Comparing all corn straw returning modes, we found that NTS was considered to be more beneficial in increasing SOC content (Table 1).…”
Section: Effects Of Corn Straw Returning Modes On Soc Contentsupporting
confidence: 89%
“…In this five-year study, retention of corn straw increased SOC content by 25.35%, 10.57% and 9.31% under NTS, MTS and CTS treatments, respectively when compared with CK in the 0-20 cm soil depth (Table 1), and coincides with previous studies (Swanepoel et al, 2018;Pu et al, 2019;Zhang et al, 2019). As a C rich substance, application of corn straw serves as a C substrate for microbes and replenishes SOC content (Ndzelu et al, 2020), thereby contributing to the build-up of SOC. Comparing all corn straw returning modes, we found that NTS was considered to be more beneficial in increasing SOC content (Table 1).…”
Section: Effects Of Corn Straw Returning Modes On Soc Contentsupporting
confidence: 89%
“…On-the-other-hand, the SOC was increased with the addition of crop residue into paddy the field with the tillage condition (Table 1), which was continuously converted into humus with the action of rhizosphere soil microorganism. The results from the previous study indicated that soil amino acid N and other compounds of N were converted into humic acid during the process of humification (Ndzelu et al, 2020). Meanwhile, our results found that rhizosphere soil acid hydrolysable N fractions and amino sugar N (ASN), amino acid N (AAN), ammonium N (AN) and hydrolysable unidentified N (HUN) contents were significantly increased by the application of conventional tillage and rotary tillage combined with crop residue incorporation management (CT and RT) (Figure 1), which were suggested that the application of tillage combined with crop residue incorporation could be a more beneficial management for improving the content of rhizosphere soil organic N in the double-cropping rice paddy field compared with treatment without crop residue input management.…”
Section: Pca Of Soil Properties Enzyme Activities Acid Hydrolysable N Fractions and N Mineralization Ratesmentioning
confidence: 99%
“…Different straw returning methods have different effects on the composition of soil humus and the structure of HA. Studies have shown that straw mulching is beneficial to the accumulation of organic carbon and humic substance C content [ 8 ] and the enhancement of functional groups such as aliphatic, hydroxyl, methoxy, and carboxyl groups on the surface soil [ 9 ], but straw mulching also affects seedling emergence and makes tillage difficult [ 10 ]. A new straw returning method had been developed, namely, straw enrichment and deep incorporation (SEDI), consisting in (1) raking the corn stalk in the field together into rows at a ratio of 4 : 1 with a finger-plate rake; (2) crushing the corn straw and burying it into subsoil, 20∼40 cm deep along designated strips with a wind-driven input cylindrical plough; (3) sowing seeds into the strips with no straw buried in between the strips with straw buried in a normal way with a nontillage seeder, to realize separation of the seeded strips (narrow rows) from the strips (wide rows) with straw buried in a wide-and-narrow row alternating cultivation mode.…”
Section: Introductionmentioning
confidence: 99%